Developing and evaluating a framework of total constraint management for improving workflow in liquefied natural gas construction - Wang, Jun; Shou, Wenchi; Wang, Xiangyu; Wu, Peng (Routledge, 2016)
© 2016 Informa UK Limited, trading as Taylor & Francis Group. Liquefied natural gas projects are complex and full of variability. Their plan reliability is affected by constraints arising from engineering, supply chains and construction site. Effective management of these constraints is critical to reducing project uncertainties and improve workflow. However, current approaches for constraint removal are fragmented and heavily rely on human’s commitments because the underlying data for decision-making are static and outdated. In order to tackle this problem, this paper proposes a framework of total constraint management (TCM), which consists of three main parts: constraint modelling, constraint monitoring and constraint removal. Information technologies (i.e. building information modelling, radio frequency identification, barcoding, laser scanning and photogrammetry) are also discussed and incorporated into the TCM framework so as to make it more practical and effective. A laboratory-based experiment was developed to demonstrate and evaluate the framework. The results showed that successful implementation of TCM could significantly improve construction workflow and productivity.